A Three‐Dimensional Branched Cobalt‐Doped α‐Fe2O3 Nanorod/MgFe2O4 Heterojunction Array as a Flexible Photoanode for Efficient Photoelectrochemical Water Oxidation1. Issue 4 (6th December 2012) - Hou, Yang; Zuo, Fan; Dagg, Alex; Feng, Pingyun
<x xml:space="preserve">Abstract</x> Hitting water with nanotrees: A three‐dimensional branched heterojunction array for water oxidation based on cobalt‐doped α‐Fe2O3 nanorod cores and MgFe2O4 shells has been synthesized. Such an architecture not only has a large surface area and excellent light absorption properties, and shows fast charge transport, but also exhibits a very high photoelectrochemical activity for water oxidation and a high stability.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>